Analisis Tematik Hadis Tentang Mushafahah Ba’da Salat Melalui Grounded Theory Johnny Saldana - Agus Irawan; Muhammad Alif; Repa Hudan Lisalam (STAI Nurul Qadim, 2025)
Mushafahah (handshaking) after prayer is a prevalent practice among Muslims, symbolizing ukhuwah (brotherhood) and social cohesion within the community. Despite its widespread adoption, there remains a divergence of scholarly opinions regarding its legal status, spiritual significance, and contextual appropriateness. This study aims to conduct a comprehensive thematic analysis of hadiths related to mushafahah ba’da salat using Johnny Saldana’s grounded theory approach. By systematically collecting and analyzing primary hadith sources alongside contemporary scholarly interpretations, the research seeks to elucidate the underlying meanings, jurisprudential rulings, and social-spiritual values embedded in this practice. The data were subjected to a rigorous coding process—initial, focused, and axial coding—to identify core themes and conceptual relationships. Findings indicate that while no explicit hadith mandates handshaking immediately following prayer, the general sunnah of mushafahah supports its permissibility and encourages it as a means of strengthening social bonds, fostering mutual respect, and facilitating the forgiveness of sins. The study also highlights ethical considerations and contextual factors influencing the practice, such as gender interactions and cultural variations. Furthermore, the research discusses the relevance and adaptation of mushafahah in contemporary Muslim societies, especially amid challenges posed by the COVID-19 pandemic, which necessitated modifications to physical greetings. This investigation contributes to Islamic social practice discourse by bridging classical prophetic traditions with modern realities, offering practical recommendations for religious educators, community leaders, and practitioners to nurture meaningful social interactions grounded in authentic Islamic teachings.